EDUCATION SYSTEM IN UK AND USA - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article describes in detail the structure and continuity of the American and UK education system, which is considered advanced today, and the stages of education in a sequence. It describes, among other things, the main functions of pre-school education, secondary education and higher education, as well as information and conclusions about the amount of credit hours allocated to classes and the grading system.